2006
DOI: 10.1016/j.ydbio.2006.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-cell pool size does matter: Defining the myogenic potency of aging skeletal muscle

Abstract: The deteriorating in vivo environment is thought to play a major role in reduced stem cell function with age. The capacity of stem cells to support tissue maintenance depends not only on their response to cues from the surrounding niche, but also on their abundance. Here, we investigate satellite cell (myogenic stem cell) pool size and its potential to participate in muscle maintenance through old age. The numbers and performance of mouse satellite cells have been analyzed using molecular markers that exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
526
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(559 citation statements)
references
References 66 publications
25
526
3
5
Order By: Relevance
“…This conclusion was supported by the finding that adding the mitogenic S100B to aged SCs in GM followed by cultivation in DM without additions resulted in a significant stimulation of MyHC expression and myotube formation (Fig. 8f) similar to what was described using bFGF (Shefer et al 2006). …”
Section: Young and Aged Scs Show Differential Expression Of Ragesupporting
confidence: 77%
“…This conclusion was supported by the finding that adding the mitogenic S100B to aged SCs in GM followed by cultivation in DM without additions resulted in a significant stimulation of MyHC expression and myotube formation (Fig. 8f) similar to what was described using bFGF (Shefer et al 2006). …”
Section: Young and Aged Scs Show Differential Expression Of Ragesupporting
confidence: 77%
“…First, the authors confirmed previous studies showing that satellite cell numbers decline with age [8,9]. It is notable that the extent of decline was variable in previous studies, as well as in the present report, likely due to the methods and markers employed (on muscle sections or isolated myofibers), muscle group examined, or other factors such as genetic strain of mice.…”
supporting
confidence: 91%
“…The ability of satellite cells to repair injured muscle markedly declines with aging (Cheung & Rando, 2013). Aside from reduced numbers of satellite cells (Garcia‐Prat, Sousa‐Victor, & Munoz‐Canoves, 2013; Shefer, Mark, Richardson, & Yablonka‐Reuveni, 2006), the differentiation capacity of satellite cells is also reduced with aging. Moreover, the number of differentiating satellite cells is decreased in aged mice, as shown by downregulation of differentiation markers such as desmin and myogenin (Charge, Brack, & Hughes, 2002; Collins, Zammit, Ruiz, Morgan, & Partridge, 2007).…”
Section: Introduction Results Discussionmentioning
confidence: 99%